The Effect of biofertilization with fungal Glomus mosseae and bacteria Bacillus subtillus and the addition of biocarbon on some physiological traits and the yield of beetroot Beta vulgaris L. (Journal of the College of Basic Education, 2025)
The experiment was conducted for the year (2023-2024) to determine the effect of biofertilization with Glomus mosseae mycorrhizal fungus and Bacillus subtillus bacteria and the addition of biocarbon on some physiological characteristics and yield and plant of beetroot. Beta vulgaris L. according to a randomized complete block design (RCBD) with three replicates for each treatment. The results were analyzed using the SPSS program. The results showed that the triple interaction treatment recorded the highest significant concentration of Betcyanins pigment in tubers, which was 40.45 mg. g-1 compared to the control treatment, which was 12.77 mg. g-1. The interaction treatment of biocarbon with bacteria achieved the highest concentration of total protein, which was 17.84%, compared to the control treatment, which was 11.16%. The results also show the positive effect of organic and biofertilization on the characteristics of the beetroot yield, as it was found that the diameter of the tubers was within the marketable yield scale, which ranged from 6.03 cm to 13.20 cm. The triple interaction treatment recorded the highest significant rate of tuber weight 759.90 g. plant-1 compared to the control treatment, which gave 126.60 g. plant-1, and the yield of the experimental unit 2279.70 g. plant-1 compared to the control treatment, which gave 379.80 g. plant-1, and the total yield is 1139.85 kg. dunum-1 compared to the control treatment, which gave 189.90 kg. Dunum-.